EFFECT OF TITANIUM NANOPARTICLES BIOSYNTHESIS BY LACTOBACILLUS CRISPATUS ON UREASE,HEMOLYSIN& BIOFILM FORMING BY SOME BACTERIA CAUSING RECURRENT UTI IN IRAQI WOMEN - Ibrahem, Kawther Hkeem; Salman, Jehan Abdul Sattar; Ali, Fattma Abodi (European Scientific Journal, ESJ, 2014)
The development of reliable and eco-friendly biosynthetic process of titanium nanoparticles acts as a vital role in the field of nano-biotechnology today. The present investigation reported that extracellular rapid biosynthesis of titanium nanoparticles using Lactobacillus crispatus isolated from heathy women vagina. The characterization of nanoparticles were carried out by atomic force Microscopy (AFM). AFM analysis was confirmed that nanoparticles size in range of (70.98 )nm. The potential of nanoparticles to control the formation of biofilms, as a function of their biocidal, antiadhesive, and delivery capabilities, is now coming under close scrutiny.biologically synthesized titanium nanoparticles played a potential role in significant higher antimicrobial efficacy against multi drug resistant caused recurrent urinary tract infection Klebsiella pneumonia, Staphylococcus aureus Acinetobacter baumani.,E.coli&Morganella morganii and its virulence factors(biofilm formation,hemolsin& urease) were found asignificant effects after treated those isolates with subMIC (16mg/ml) titanium nanoparticle together and cultured on their special media .Our results showed that TI-NP had inhibitory effect against recurrent UTI causative bacteria at concentration (32) mg\ml &TI nanoparticles with appropriate concentration (16)mg/ml could show significant reduction in biofilm formation.hemolysin &urease production..